Cameroon's Social Democratic Front : Its History and Prospects as an Opposition Political Party (1990-2011). - Krieger, Milton H. (Langaa RPCIG, 2008)
Cameroon's Social Democratic Front (SDF) was among the watershed challenges c.1990 by sub-Saharan Africa's democratization forces against autocratic regimes, but it crested in 1992 and has subsided since. Yet the party survives, participates in the National Assembly, maintains a grass roots structure, and prepares for a presidential ballot in 2011 that will likely determine its fate. The author conducted research four times in Cameroon, 1989-1999, focusing on the SDF since 1991, and maintains party contacts to the present. The book assesses its history and its prospects, covering the SDF in Af.